(untitled) (Perner’s Contacts, 2017)
The paper deals with the problem of designing warehouses from a global perspective. The paper presents the results of a brief analysis of publications dealing with the issue. As the analysis shows, many authors deal either complexly or with isolated problems. Another part of the paper is the definition of the problems which need to be addressed to design of the warehouse at the strategic, tactical and operational level. Four main areas of warehouse design are at the end of the paper.